2020
DOI: 10.1016/j.ajog.2020.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Foley and prostaglandins versus Foley and oxytocin for cervical ripening: a network meta-analysis

Abstract: BACKGROUND: Trial and meta-analysis data revealed a reduction in time to delivery for Foley and prostaglandins or Foley and oxytocin vs Foley alone. However, there are limited data for the comparison of the 2 combination methods against each other. OBJECTIVE: This study aimed to determine whether Foley and prostaglandins or Foley and oxytocin decrease the time to vaginal delivery using a network meta-analysis. STUDY DESIGN: A network meta-analysis (PROSPERO CRD42018081948) was performed comparing Foley and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 56 publications
(38 reference statements)
3
23
0
Order By: Relevance
“…Interestingly, the mechanical methods were associated with lower rates of tachysystoles and the rates of cesarean sections were comparable to the pharmacological methods (27). Similar to what has been found in our review, the mechanical methods were found to be associated with a short period of induction of labor and no difference was found between concurrent Foley catheter and oxytocin vs. Misoprostol and Foley catheter (28).…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, the mechanical methods were associated with lower rates of tachysystoles and the rates of cesarean sections were comparable to the pharmacological methods (27). Similar to what has been found in our review, the mechanical methods were found to be associated with a short period of induction of labor and no difference was found between concurrent Foley catheter and oxytocin vs. Misoprostol and Foley catheter (28).…”
Section: Discussionsupporting
confidence: 85%
“…It has been suggested that parity may affect how effective this combined intervention is. 7−9 The primary trial 4 and the trial by Levine and colleagues 6 did not find that parity played a role in decreasing the time to delivery with the combination of a Foley catheter and oxytocin administration. This remains true because the time to delivery adjusted for parity status, first Bishop score, and BMI remained shorter in the Foley with oxytocin group in our study.…”
Section: Resultsmentioning
confidence: 99%
“…It seems that Cook's balloon catheter, invented in the early 90's, may be more effective in preinduction cervical ripening compared to Foley's catheter and PGE2 prostaglandin [ 14 , 15 ]. Studies indicate that the combination of mechanical method with vaginal prostaglandins does not bring additional benefits such as reduction time to vaginal delivery or reduction in cesarean section rate [ 16 ].…”
Section: Discussionmentioning
confidence: 99%